2012
DOI: 10.1161/circulationaha.111.058719
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Use of Cardiopulmonary Exercise Testing Identifies Adults With Congenital Heart Disease at Increased Mortality Risk in the Medium Term

Abstract: Background-Parameters of cardiopulmonary exercise testing were recently identified as strong predictors of mortality in adults with congenital heart disease. We hypothesized that combinations of cardiopulmonary exercise testing parameters may provide optimal prognostic information on midterm survival in this population. Methods and Results-A total of 1375 consecutive adult patients with congenital heart disease (age, 33Ϯ13 years) underwent cardiopulmonary exercise testing at a single center over a period of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(164 citation statements)
references
References 54 publications
7
146
2
9
Order By: Relevance
“…The integration of the two approaches is appealing, as RSF is a nonparametric method, successfully applied in a variety of clinical scenarios (19)(20)(21). It accounts for censored data, refrains for assumptions on data distribution, and allows for feature selection, whereas Cox modeling is easy to interpret and frequently used in clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The integration of the two approaches is appealing, as RSF is a nonparametric method, successfully applied in a variety of clinical scenarios (19)(20)(21). It accounts for censored data, refrains for assumptions on data distribution, and allows for feature selection, whereas Cox modeling is easy to interpret and frequently used in clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…A threshold for variable importance was determined through a nested RSF approach (21), estimating a cut-off for predictive contribution by serially introducing variables into RSF models according to their importance, while measuring improvement in the C-index. For instance, in the first iteration, the top ranking variable was introduced; in the second, the top two variables; and so on.…”
Section: Translational Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…76 They showed that cardiopulmonary exercise testing provides strong prognostic information in adult patients with congenital heart disease. However, they considered prognostication should be approached differently, depending on the presence of cyanosis, use of rate-lowering drugs and achieved level of exercise.…”
Section: Adult Congenital Heart Diseasementioning
confidence: 99%
“…4 More recently, studies have shown that decreased exercise performance is associated with an increased risk of early death. 5,6 Exercise stress test data might then uncover circulatory limitations not seen in the at-rest patient. We reviewed our institution's experience and sought to determine the association between a patient's age at performance of the Fontan procedure and his or her aerobic performance, as measured by the percentage of predicted maximum oxygen consumption (Vo 2 ).…”
mentioning
confidence: 99%